2006
DOI: 10.1207/s15324796abm3103_8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of group-based cognitive-behavioral stress management in localized prostate cancer: Development of stress management skills improves quality of life and benefit finding

Abstract: Results support the use of group-based cognitive-behavioral interventions in promoting QoL and BF in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
187
1
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(206 citation statements)
references
References 60 publications
11
187
1
7
Order By: Relevance
“…90 Cognitive --behavioral training used in these studies was positively linked with effectiveness of intervention and suggests a relevant and fruitful approach to delivery. 91 Group sessions have been effective among prostate cancer survivors, as indeed they have among other populations of male patients, but the personal nature of men's issues in prostate cancer survivorship suggests that many men will benefit from one-to-one involvement within an intervention. 92 An intervention offering both opportunities would be valuable.…”
Section: Psychological Issues In Prostate Cancer Related To Developmementioning
confidence: 99%
“…90 Cognitive --behavioral training used in these studies was positively linked with effectiveness of intervention and suggests a relevant and fruitful approach to delivery. 91 Group sessions have been effective among prostate cancer survivors, as indeed they have among other populations of male patients, but the personal nature of men's issues in prostate cancer survivorship suggests that many men will benefit from one-to-one involvement within an intervention. 92 An intervention offering both opportunities would be valuable.…”
Section: Psychological Issues In Prostate Cancer Related To Developmementioning
confidence: 99%
“…35 Prior work has indicated that psychological interventions directed at psychoeducation or teaching stress management skills can improve aspects of quality of life in men recovering from PCa treatment. [38][39] Less is known about how these interventions affect physical recovery-including recovery of sexual functioning-after medical treatments are completed. The present study addressed this gap and also tested the role of interpersonal sensitivity as a possible moderator of intervention effects.…”
Section: Psychological Interventions For Men Recovering From Prostatementioning
confidence: 99%
“…The ISBF questionnaire is based on the 17 items of the Measure of Current Status (MOCS), a questionnaire in English language (Carver, 2005) that has been developed and used to test the effectiveness of stress management trainings in cancer patients (Penedo et al, 2003;Penedo et al, 2004;Antoni et al, 2006;Penedo et al, 2006). The MOCS was designed to assess perceived management skills (i.e., the perceived ability to respond to the challenges and demands of everyday life).…”
Section: Assessment Of Stress Management Skillsmentioning
confidence: 99%
“…"I cannot do this at all" to "I can do this extremely well"). Hitherto, psychometric properties of the MOCS have only been investigated in cancer patients with either prostate cancer (Penedo et al, 2003;Penedo et al, 2004;Penedo et al, 2006) or breast cancer . In these samples, the factor structure and internal consistency of the MOCS have been tested but results differ (for details see Supplemental Material 3).…”
Section: Assessment Of Stress Management Skillsmentioning
confidence: 99%
See 1 more Smart Citation